Heckscher on the Slow Monetization of Sweden and His Incidental Refutation of Jevons and Menger - Klas Fregert (Lund University, School of Economics and Management, Department of Economics, 2015)
Eli F. Heckscher found that in 16th century Sweden: 1) indirect barter was the most common exchange method and 2) monetary exchange was carried out with different coins, none a generally accepted medium of exchange. These findings refute the search and transaction cost models of the emergence of money, which build on Jevons (1875) and Menger (1892). Instead, following up on Heckscher's suggestions, Alchian's (1977) model of money as the most saleable good by being the least costly to evaluate should be the basis for a positive theory of monetization. An increased quality of money causes monetization, which in turn spurs specialization in production. In addition, the government by demanding monetary payments of taxes and expenditures can force agents to overcome high initial costs of switching from barter to monetary exchange.
Keywords: B22; E40; N13; 330; monetization; Sweden; microfoundations of money; indirect barter; monetary exchange; double coincidence of wants